Antithrombotic agents and effect on outcomes in ischemic stroke with atrial fibrillation and large artery atherosclerosis: a real-world study - Chen, Jilu; Cheng, Jianhua; Ye, Qiang; Liu, Yuntao; Zhang, Yanlei; Zhang, Zheng (Frontiers in Neurology, 2025)
IntroductionThe optimal antithrombotic regimen for preventing recurrent stroke in patients who experience ischemic stroke due to atrial fibrillation (AF) and atherosclerotic large-vessel stenosis remains unclear. The present study aimed to evaluate the effect of multiple antithrombotic therapies on outcomes after ischemic stroke due to ≥ 2 causes.MethodsData from 632 patients at a single hospital, who experienced ischemic stroke due to AF and large-artery atherosclerosis. Patients were categorized into 3 groups according to antithrombotic therapy at discharge: antiplatelets (APT), oral anticoagulant(s) (OAC), and APT plus OAC. Study outcomes included recurrent ischemic stroke and composite outcomes for cardiovascular events, death and major bleeding. Propensity scores (PS) were used to balance APT and OAC groups.ResultsAmong 632 patients, 158 (25.0%) were treated with APT, 447 (70.7%) with OAC, and 27 (4.3%) with both APT and OAC. After applying PS, only OAC had a significant beneficial effect on the composite outcome (hazard ratio [HR] 0.41 [95% confidence interval (CI) 0.19–0.83]; p = 0.01) and death (HR 0.12 [95% CI 0.01–1.0]; p = 0.05). However, there was no significant difference in one-year recurrent stroke events or risk for bleeding between the APT and OAC groups. Further analysis of the relationship between the dose of OAC and outcome revealed no significant difference between reduced and standard doses of OAC.ConclusionThis study demonstrated that OAC monotherapy was associated with a lower risk for composite outcomes and death after ischemic stroke due to AF and atherosclerotic stenosis, although the OAC dose had no effect on clinical outcomes.